Dicephalous Derodymus Tetrabrachius Tetrapus Omphalopagus Dicaudatus Monster with Single Twin Limb Ankylosis in a Murrah Buffalo - Singh Sidhu, Tanvir; Nain, Dipti; Singh Sandhu, Gurbeer; Kumar, Ajeet (The Indian Journal of Animal Reproduction, 2025)
A 7 year old pluriparous Murrah buffalo with history of dystocia was presented at Obstetrics unit, GADVASU, Ludhiana. Per-vaginal examination revealed the presence of four fore-limbs, two heads suggesting dystocia due to congenital twins. Following further examination, fetotomy was decided as operation of choice to deliver the fetus. Under epidural anaes thesia, partial fetotomy with single cut near the joining of twins was done leading to delivery of Dicephalous Derodymus Tetrabrachius Tetrapus Omphalopagus Dicaudatus fetal monster with limbs ankylosis in only one fetus.